2014
DOI: 10.1073/pnas.1409513111
|View full text |Cite
|
Sign up to set email alerts
|

α 2A adrenergic receptor promotes amyloidogenesis through disrupting APP-SorLA interaction

Abstract: Accumulation of amyloid β (Aβ) peptides in the brain is the key pathogenic factor driving Alzheimer's disease (AD). Endocytic sorting of amyloid precursor protein (APP) mediated by the vacuolar protein sorting (Vps10) family of receptors plays a decisive role in controlling the outcome of APP proteolytic processing and Aβ generation. Here we report for the first time to our knowledge that this process is regulated by a G protein-coupled receptor, the α 2A adrenergic receptor (α 2A AR). Genetic deficiency of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 34 publications
4
51
0
2
Order By: Relevance
“…ATI also enhances motor recovery after two types of brain injury (TBI -present study; stroke - Puurunen et al, 2001). Moreover, the recently discovered favorable α2A-adrenergic receptor blockade-mediated effects on antiamyloidogenesis and insulin secretion could provide additional benefits for the use of noradrenergic α2A-antagonists in the treatment of TBI (Gribble, 2010;Chen et al, 2014). Therefore, we consider that further studies are warranted to investigate proconvulsant 2-adrenergic blockade and its downstream signaling as a therapeutic target for recovery enhancement and antiepileptogenesis in order to combat the development of co-morbidities after TBI.…”
Section: Discussionmentioning
confidence: 82%
“…ATI also enhances motor recovery after two types of brain injury (TBI -present study; stroke - Puurunen et al, 2001). Moreover, the recently discovered favorable α2A-adrenergic receptor blockade-mediated effects on antiamyloidogenesis and insulin secretion could provide additional benefits for the use of noradrenergic α2A-antagonists in the treatment of TBI (Gribble, 2010;Chen et al, 2014). Therefore, we consider that further studies are warranted to investigate proconvulsant 2-adrenergic blockade and its downstream signaling as a therapeutic target for recovery enhancement and antiepileptogenesis in order to combat the development of co-morbidities after TBI.…”
Section: Discussionmentioning
confidence: 82%
“…Beneficial actions of an a2-antagonist have been described in the transgenic amyloid precursor protein (APP)/PS1 mouse model of AD (Chen et al 2014). In those studies, treatment with the a2-antagonist idazoxan for 10 weeks reduced Ab burden in the hippocampus and cortex, and improved short-term memory in a novel object recognition test and spatial memory in the Morris water maze test.…”
Section: Anti-inflammatory and Neuroprotective Actions Of Raising Na mentioning
confidence: 99%
“…We have demonstrated that stimulation of a 2A AR promotes amyloidogenic processing of APP through activation of G i/o proteins (23). The direct interaction between APP and a 2A AR would bring APP to the proximity of a 2A AR downstream signaling to modulate its processing route.…”
Section: Discussionmentioning
confidence: 88%
“…Using the BbsI restriction enzyme, the primers were introduced to the pSpCas9(BB)-2A-GFP plasmid. An N2a-HA-a 2A AR stable cell line (23) was transfected with the resulting plasmid using Lipofectamine 2000 and selected for GFP expression by fluorescence-activated cell sorting. Single clones were allowed to grow and screened for loss of expression of APP.…”
Section: Cell Culturementioning
confidence: 99%